#### Answer

$-\sqrt 57$

#### Work Step by Step

$\sqrt -3\times\sqrt -19=i\sqrt 3\times i\sqrt 19=i^{2}\sqrt (3\times19)=i^{2}\sqrt 57=-1\times\sqrt 57=-\sqrt 57$
We know that $\sqrt -1=i$, because $i^{2}=-1$.

Published by
Pearson

ISBN 10:
0321969359

ISBN 13:
978-0-32196-935-4

$-\sqrt 57$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.